Connection of Jonsson theory with some Jonsson polygons theories - Yeshkeyev, A.R.; Urken, G.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The main result of this article is connected with some Jonsson theory of polygons and is devoted to obtaining a description of the characteristic of such polygons using invariants related to them. With this limited consideration (the group is a strong particular case of a monoid) were obtained for such a theory of the property of perfection and Jonsson property. Thus, for some existential complete and perfect Jonsson theories, there is the same Jonsson theory of polygons, in which two Jonsson theories are syntactically similar.
Кейбiр йонсондық теория полигондарымен йонсондық теорияның байланысы
Связь йонсоновской теории с некоторой йонсоновской теорией полигонов
Keywords: Jonsson theory; semantic model; perfect theory; polygon; model companion; syntactic and semantic similarity of Jonsson theories